Pemberdayaan Tim “Jumantik” (Juru Pemantau Jentik) di SD 14 dan 15 Koto Lalang pada Masa Pandemi - Masrizal Masrizal; Muhammad Alfarezi; Ade Betasril; Trif Vando Rahmalber (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Schools, apart from functioning as places of learning, can also be a threat of disease transmission if they are not appropriately managed. School age for children is also a period prone to various diseases, such as diarrhoea, infectious diseases, dengue fever, etc. In response to this problem, the formation and empowerment of the